STUDI KUALITAS AIR SUNGAI KALILO, BANYUWANGI: ANALISIS BIOLOGICAL OXYGEN DEMAND (BOD) DAN IMPLIKASINYA TERHADAP EKOSISTEM - Kayumi Meilana, Yuristya; Dagsy, Irqami Rachma Dwi (JURNAL BIOSENSE, 2025)
The Kalilo River in Banyuwangi plays a vital role in supporting ecosystems and community activities but faces ecological pressures due to human activities. This study aims to analyze the Biological Oxygen Demand (BOD) levels at the upstream and downstream sections of the Kalilo River and their impact on the ecosystem. The research was conducted in December 2024 using standard BOD testing methods through a quantitative and qualitative approach. Water samples were collected from Grogol Village (upstream) and Kampung Ujung Neighborhood (downstream) and tested at the Environmental Laboratory of Banyuwangi Environmental Agency. Results showed that BOD levels were 0.32 mg/L upstream and 1.33 mg/L downstream. Although both sites met the class II water quality standards (≤ 3 mg/L) according to Government Regulation No. 22 of 2021, the higher BOD level downstream indicated organic pollution from domestic activities. The ecological impact includes reduced dissolved oxygen levels, potentially disrupting aquatic life. This study highlights the importance of waste management and continuous water quality monitoring to ensure the sustainability of the Kalilo River ecosystem.